Changes in canal diameter and cervical lordosis in patients who underwent en-bloc laminoplasty for the treatment of cervical spinal stenosis - Meral, Mehmet; Koç, Rahmi Kemal (The European Research Journal, 2024)
Objective: Cervical spinal canal-expanding laminoplasty has been recognized as an alternative to cervical laminectomy, especially in multilevel cervical myelopathy due to spinal stenosis. This study aimed to determine the effects of En-block laminoplasty on cervical sagittal balance, cervical spine biomechanics and whether it is sufficient to preserve cervical canal diameter and lordosis and whether it causes additional lordosis or kyphosis in cases of cervical narrow spinal canal. Methods: Thirty-eight cervical narrow canal patients operated on between 2008 and 2020 were retrospectively evaluated and the results of 24 laminoplasty patients were evaluated. Spinal tomography results for the evaluation of canal diameter changes and X-ray results for cervical sagittal balance evaluation were compared with each other in the early postoperative period and 3 years later. For cervical lordosis assessment, Cobb and C2-C7sagital vertical axis measurements were performed using the PACS system. Results: Fifteen patients were male and 9 were female. The mean age was 65.55±11.56 years (min-max: 58-84) and the mean follow-up period was three years. Two patients had one level stenosis, 4 had two levels, 7 had three levels, and 11 had four or more levels. Radiculopathy was present in 17 patients (71.8%) and myelopathy in 7 patients (29.1%). There was no statistically significant difference in the frequency of myelopathy/radiculopathy between genders. When all distances were considered, no statistical difference was observed in the early postoperative period (median ten days) and late postoperative period (median 3 years) in terms of canal diameters. No measurement value could be obtained for any level diagnosed as restenosis or requiring reoperation. Loss of lordosis was measured in only one patient. Otherwise, lordosis was preserved in all cases at late conversion. Conclusions: The results of our study showed that en-block laminoplasty after the cervical narrow spinal canal was sufficient to maintain the cervical canal diameter in the long term with appropriate patient and surgical technique.